Photoetched micro-patterned mechanically stable TNTs film and application thereof

Through photolithography micropatterning technology, the TNTs film embedded in grooves is formed on the titanium implant, which solves the problem of TNTs being prone to cracking and peeling during chewing, significantly improves the anti-peel and wear resistance, and enhances the mechanical of the implant Stability and osteogenesis ability.

CN119194558APending Publication Date: 2024-12-27STOMATOLOGICAL HOSPITAL AFFILIATED TO WENZHOU MEDICAL UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411345318.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Titanium dioxide nanotubes (TNTs) on titanium implants are prone to cracking and peeling during chewing, resulting in friction and wear, affecting the long-term service life of the implant.

Method used

The hierarchical micro-patterning technology is used to form a groove structure on the surface of titanium-based materials, and TNTs are embedded. The layered micro-patterned TNTs film with interlocking concave structure is prepared by spin-coating photoresist, ultraviolet exposure, development, anodizing and other steps. , enhance its anti-peel and wear resistance.

Benefits of technology

It significantly improves the anti-stripping and wear resistance of TNTs, avoids direct contact between nanotubes and bone interfaces, reduces the influence of friction, enhances mechanical stability and osteoblast growth ability, and becomes an ideal platform for multifunctional implants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194558A_ABST
    Figure CN119194558A_ABST
Patent Text Reader

Abstract

The invention relates to the field of titanium and titanium alloy processing, in particular to a photoetching micro-patterning mechanically-stable TNTs film and application thereof, and a preparation method of the photoetching micro-patterning mechanically-stable TNTs film comprises the following steps: (1) carrying out alkali heat treatment on the surface of a titanium-based material; (2) spin-coating photoresist on the surface of the titanium-based material subjected to alkali heat treatment; (3) covering the photoresist by using a mask, and exposing by using ultraviolet light; (4) soaking the exposed titanium-based material in a developing solution; (5) the titanium-based material obtained in the step (4) is soaked in etching liquid, and then ultrasonic cleaning and baking are conducted; (6) carrying out anodic oxidation on the etched region; (7) the photoresist is removed, and a mechanically stable TNTs thin film subjected to photoetching micro-patterning is obtained; the surface structure of the mechanically stable TNTs thin film subjected to photoetching micro-patterning is that TNTs are embedded in a groove formed by etching. Different pattern masks are manufactured through photoetching and wet etching technologies, square, hexagonal and circular (S / H / R) micro-patterns TNTs are formed, and higher stripping resistance and wear resistance are shown; in addition, the micro-pattern TNTs reserve a nanotube structure, so that the growth and differentiation of osteoblasts are facilitated; the micro-pattern TNTs show optimal coating mechanical stability, cytocompatibility and osteogenesis performance in an experimental group, and become an ideal platform for developing a multifunctional implant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of titanium and titanium alloy processing, in particular to a mechanically stable TNTs film formed by photolithography micro-patterning and application thereof. Background Art

[0002] Tooth loss due to caries and periodontal disease is a widespread public health problem. Dental implants are considered the best treatment for missing teeth, and titanium (Ti) remains the preferred implant material. However, titanium is bioinert when treating patients with metabolic diseases such as osteoporosis and diabetes. To address this issue, researchers have used a variety of techniques to impart functionality to Ti substrates, including the formation of nanostructures on their surfaces. Nanostructures on Ti substrates are mainly divided into two categories: porous and non-porous. Among them, porous structures are more suitable for dental implant restorations aimed at restoring chewing function due to their ability to reduce stress shielding effects. Titanium dioxide nanotube (TNTs) coatings formed on Ti surfaces by electrochemical anodization are particularly attractive. Among the porous nanostructures, titanium dioxide nanotube (TNTs) coatings formed on Ti surfaces by electrochemical anodization are considered the best choice. TNTs enhance osteogenesis by improving the adhesion of osteoblasts. In addition, due to their porous nanoscale structure, TNTs also provide stress buffering effects, better load distribution, and energy dissipation under chewing pressure, thereby extending the service life of implants. Furthermore, the uniform and controllable tubular size of TNTs, as well as their dual charge properties, make them suitable for the delivery of bioactive metal ions, proteins, and drugs, showing their wide application and great development potential in the biomedical field.

[0003] Although TNTs have great potential in advanced dental implant technology, they are prone to cracking and flaking under mechanical stress. For dental implants that undergo surgical implantation and are subjected to continuous multi-directional chewing forces, it is crucial to address the mechanical stability of TNTs. Excessive chewing pressure may lead to cracking, flaking, and debris formation of TNTs in dental implants, similar to chips in friction and wear testing. This may trigger an immune-inflammatory response, hinder bone integration, and affect the long-term service life of TNTs implants, becoming a major obstacle from laboratory to clinical application.

[0004] To enhance the stability of TNTs on Ti implants, various methods have been proposed. Some scholars have explored the incorporation of metal nanoparticles to develop a titanium nanotube-silver / gold nanoparticle hybrid structure and evaluated its stability in aqueous solution. By adjusting the surface structure of the TiN hard coating, a transparent superhydrophobic F-TNTs / TiN coating with strong and durable properties was innovatively prepared, which significantly enhanced the stability of the TNTs coating. The researchers developed titanium dioxide nanotube arrays with superior mechanical properties by using an optimized electrochemical anodization system and fixing the D-amino acid K122-4 peptide through a dopamine membrane. Some researchers enhanced the stability of the TNT coating by changing the sputtering power and the surface roughness of the substrate. Although these methods significantly improved the stability of TNTs, they were still insufficient to prevent the peeling and friction wear of implants during chewing due to the limitations of the thin-walled structure of TNTs.

[0005] Therefore, to enhance the stability of TNTs on anodized Ti implants, a hierarchical micropattern structure with interlocking convex and concave structures can be used to prevent direct contact between the nanotubes and the bone interface, thereby avoiding the influence of friction. In this study, different pattern masks, including three micropatterns of square, hexagonal, and circular (S / H / R), were fabricated by photolithography and wet etching techniques to selectively remove the photoresist in the designated areas. Subsequently, anodization was directly performed on the etched micropattern area to form improved TNTs. To date, no research in this area has been reported. Summary of the invention

[0006] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is how to effectively prevent the peeling and friction wear of TNTs on the surface of Ti material during chewing, and enhance its anti-peeling and wear resistance.

[0007] To achieve the above object, the present invention provides a method for preparing a mechanically stable TNTs film by photolithographic micropatterning, comprising the following steps:

[0008] (1) performing alkali heat treatment on the surface of the titanium-based material;

[0009] (2) spin coating a photoresist on the surface of the titanium-based material subjected to alkali heat treatment;

[0010] (3) Use a mask to cover the photoresist and expose it with ultraviolet light;

[0011] (4) soaking the exposed titanium-based material in a developer;

[0012] (5) soaking the titanium-based material obtained in step (4) in an etching solution, and then ultrasonically cleaning and baking;

[0013] (6) anodizing the etched area;

[0014] (7) removing the photoresist to obtain a photolithographically micropatterned mechanically stable TNTs film;

[0015] The mechanically stable TNTs film surface structure formed by photolithographic micropatterning is that TNTs are embedded in the grooves formed by etching.

[0016] Preferably, the micropattern is square, hexagonal or circular. Optionally, the diagonal diameter of the micropattern is 50-600 μm.

[0017] Preferably, the depth of the stripe pattern is 10-50 μm, and preferably, the depth of the stripe pattern is 20 μm.

[0018] Preferably, the ultraviolet light wavelength used for the ultraviolet light exposure is 365 nm, and the exposure time is 30-120 seconds.

[0019] Preferably, the exposure duration is 90 seconds.

[0020] Preferably, the alkali heat treatment in step (1) is performed using 1-10 mol / L NaOH solution at 70-90° C. for 12-48 hours.

[0021] Preferably, the concentration of the NaOH solution is 5 mol / L, the temperature is 80° C., and the treatment time is 24 hours.

[0022] Preferably, the etching solution comprises deionized water, nitric acid and hydrofluoric acid, and the ratio of deionized water, nitric acid and hydrofluoric acid is 1:1:9.

[0023] Preferably, the electrolyte used for anodization in step (6) comprises deionized water, glycerol and ammonium fluoride, and the ratio of deionized water, glycerol and ammonium fluoride is 50:50:1.

[0024] Preferably, the voltage of the anodization in step (6) is 10-100 V and the time is 0.5-1.5 h.

[0025] Preferably, the voltage of the anodization is 30 V and the time is 1 hour.

[0026] Preferably, the step of spin coating the photoresist in step (2) is to use a spin coater to spin coat 5-15 μL of photoresist at a speed of 2000-4000 rpm for 10-50 seconds to coat the micro-patterned TNTs sample.

[0027] Preferably, the soaking time in the developer in step (4) is 5-10 minutes.

[0028] Preferably, the soaking time of the developer is 8 minutes.

[0029] In a preferred embodiment of the present invention, the present invention provides a photolithographically micropatterned mechanically stable TNTs film, which is prepared by the above method.

[0030] In another preferred embodiment of the present invention, the present invention provides a titanium-based dental implant modified with a photolithographically micropatterned mechanically stable TNTs film.

[0031] In another preferred embodiment of the present invention, the present invention provides the use of the photolithographic micropatterned mechanically stable TNTs film described in the present invention in improving the wear resistance and osteogenic differentiation ability of titanium implants.

[0032] The outstanding features and beneficial effects of the present invention are:

[0033] The anti-stripping micro-patterned TNTs array film of the present invention utilizes a hierarchical micro-pattern structure with an interlocking convex-concave structure to prevent direct contact between the nanotubes and the bone interface, thereby avoiding the influence of friction. The present invention uses photolithography and wet etching techniques to produce different pattern masks to form square, hexagonal and circular (S / H / R) micro-patterned TNTs, which show stronger anti-stripping and wear resistance than traditional TNTs; in addition, the micro-patterned TNTs retain the nanotube structure to facilitate osteoblast growth and differentiation; the micro-patterned TNTs show the best coating mechanical stability, cell compatibility and osteogenic performance in the experimental group, becoming an ideal platform for the development of multifunctional implants.

[0034] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Characterization of TNTs and square TNTs. (A) OM and SEM images; (B) RR and EDS images; (C) Diameter measurement of gradient square micropatterned TNTs at 50 μm, 150 μm, 300 μm, and 600 μm diameters; (D) Surface roughness analysis; (E) Water contact angle measurement. Statistical significance is indicated by *(p<0.05) and **(p<0.01).

[0036] Figure 2 Characterization of TNTs and hexagonal TNTs. (A) OM and SEM images; (B) RR and EDS images; (C) Diameter measurements of gradient hexagonal micropatterned TNTs at 50 μm, 150 μm, 300 μm, and 600 μm diameters; (D) Surface roughness analysis; (E) Water contact angle measurement. Statistical significance is indicated by *(p<0.05) and **(p<0.01).

[0037] Figure 3 Characterization of TNTs and circular TNTs. (A) OM and SEM images; (B) RR and EDS images; (C) Diameter measurement of gradient circular micropatterned TNTs at 50 μm, 150 μm, 300 μm, and 600 μm diameters; (D) Surface roughness analysis; (E) Water contact angle measurement. Statistical significance is indicated by *(p<0.05) and **(p<0.01).

[0038] Figure 4 Figure 1. Stability evaluation of TNTs: friction and wear tests under three lubrication conditions. (A) OM, SEM, RR and EDS images of control TNTs; (B1) Schematic diagram of adhesion test by applying and then peeling off the tape; (B2) OM, SEM and RR images of control TNTs; (C1) Schematic diagram of friction and wear test; (C2) Optical microscopy (OM) image after friction and wear test; (D) Inverted fluorescence microscopy (IFM) image of MC3T3-E1 cells on control TNTs.

[0039] Figure 5 Stability evaluation of TNTs and square TNTs: peel test. (A) OM, SEM and RR images after peel test; (B1-5) deformation-force curves; (C) statistical analysis of maximum tensile force. Statistical significance is indicated by * (p < 0.05).

[0040] Figure 6 Stability evaluation of TNTs and hexagonal TNTs: peel test. (A) OM, SEM and RR images after peel test; (B1-5) deformation-force curves; (C) statistical analysis of maximum tensile force. Statistical significance is indicated by * (p < 0.05).

[0041] Figure 7 Stability evaluation of TNTs and round TNTs: peel test. (A) OM, SEM and RR images after peel test; (B1-5) deformation-force curves; (C) statistical analysis of maximum tensile force. Statistical significance is indicated by * (p < 0.05).

[0042] Figure 8 Stability evaluation of TNTs and square TNTs: friction and wear tests under three lubrication conditions. (A) Optical microscope (OM) images after friction and wear tests; (B) Statistical analysis of wear width; (C) Statistical analysis of average friction coefficient. Statistical significance is marked with * (p < 0.05) and ** (p < 0.01).

[0043] Fig. 9Stability evaluation of is-TNTs and hexagonal TNTs: friction and wear tests under three lubrication conditions. (A) Optical microscopy (OM) images after friction and wear tests; (B) Statistical analysis of wear width; (C) Statistical analysis of average friction coefficient. Statistical significance is marked with * (p < 0.05) and ** (p < 0.01).

[0044] Fig.10 Stability evaluation of TNTs and circular TNTs: friction and wear tests under three lubrication conditions. (A) Optical microscope (OM) images after friction and wear tests; (B) Statistical analysis of wear width; (C) Statistical analysis of average friction coefficient. Statistical significance is marked with * (p < 0.05) and ** (p < 0.01).

[0045] Fig.11 In vitro viability assessment of TNTs and square TNTs. (A) Inverted fluorescence microscopy (IFM) images of MC3T3-E1 cells on samples; (B) Statistical analysis of early adhesion; (C, D) Cell viability results; (E, F) ALP detection; (G) Mineralization staining at 14 days. Statistical significance is marked as * (p < 0.05), ** (p < 0.01) and ns (p > 0.01).

[0046] Fig.12 In vitro viability assessment of TNTs and hexagonal TNTs. (A) Inverted fluorescence microscopy (IFM) images of MC3T3-E1 cells on samples; (B) Statistical analysis of early adhesion; (C, D) Cell viability results; (E, F) ALP detection; (G) Mineralization staining at 14 days. Statistical significance is marked as * (p < 0.05), ** (p < 0.01) and ns (p > 0.01).

[0047] Fig.13 In vitro viability assessment of TNTs and round TNTs. (A) Inverted fluorescence microscopy (IFM) images of MC3T3-E1 cells on samples; (B) Statistical analysis of early adhesion; (C, D) Cell viability results; (E, F) ALP detection; (G) Mineralization staining at 14 days. Statistical significance is marked as * (p < 0.05), ** (p < 0.01) and ns (p > 0.01). DETAILED DESCRIPTION

[0048] The following describes several preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.

[0049] Material

[0050] Ti plates were provided by Baoji Fuxin Metal Co., Ltd. (Shaanxi, China). Ti implants were provided by Zhuo Shiyou Co., Ltd. (Zhejiang, China). Photoresists, developers, and photoresist removers were provided by CITIC Qiheng Co., Ltd. (Jiangsu, China). UV lithography equipment was provided by the Institute of Optoelectronics, Chinese Academy of Sciences (Sichuan, China). Photolithography masks were manufactured by Nanjing Qingwei Electronic Technology Co., Ltd. (Jiangsu, China), and the mask patterns included micro square patterns (S), micro hexagonal patterns (H), and micro circular patterns (R), and the diagonal diameters of each pattern were 50 μm, 150 μm, 300 μm, and 600 μm, respectively. All other reagents were provided by Aladdin Industrial Co., Ltd. (Shanghai, China).

[0051] Example 1 Preparation and Characterization of TNTs and L-TNTs Samples

[0052] TNTs sheets (10 × 10 × 0.2 mm) and TNTs implants (8 mm in length and 3 mm in diameter) were prepared by electrochemical anodization process. The process was carried out at a constant voltage of 30 V for 1 h. The electrolyte solution consisted of deionized water, glycerol, and ammonium fluoride mixed in a ratio of 50:50:1.

[0053] The preparation of S / H / R-TNTs includes the following seven steps:

[0054] (1) The sample was subjected to alkaline heat treatment in a 5 mol / L NaOH solution at 80°C for 24 hours.

[0055] (2) Use a spin coater to evenly coat 10 μL of photoresist on the sample at a spin coating speed of 3000 rpm for 20 seconds.

[0056] (3) Using customized S, H, and R photolithography masks, expose to 365 nm UV light for 90 seconds.

[0057] (4) Soak the sample in the developer for 8 minutes.

[0058] (5) The sample was immersed in an etching solution composed of deionized water, nitric acid and hydrofluoric acid in a ratio of 1:1:9 for 10 seconds, then rinsed, ultrasonically cleaned and baked at 100°C for 20 minutes.

[0059] (6) In the selective electrochemical anodization step, the sample is anodized in the same electrolytic environment as the TNTs, and the photoresist-covered areas are protected from anodization, thereby isolating the wet-etched areas for specific modification.

[0060] (7) The photoresist is removed using a remover. The obtained samples are marked as S50, S150, S300, S600; H50, H150, H300, H600; R50, R150, R300, R600.

[0061] The morphological analysis of TNTs and S / H / R-TNTs samples was performed by optical microscopy (OM, Zeiss, Germany, model A1) and scanning electron microscopy (SEM, Hitachi, Japan, model S-4800). The surface properties were measured by a roughness reconstruction system (RR, Phenom, the Netherlands, model XL), and the wettability was evaluated using a contact angle meter (Chongqing, China, model JGW-360A).

[0062] In this study, OM, SEM, RR and EDS were used to investigate the surface properties of TNTs and S-TNTs, H-TNTs and R-TNTs (S / H / R-TNTs). Figure 4 A shows the surface characteristics and composition analysis of the control group TNTs. The OM, SEM, and RR images show the uniform microstructure of the sample surface, which is a more ordered and smooth tubular structure. EDS analysis results show that the sample is mainly composed of titanium and oxygen, which is consistent with the expected composition of titanium nanotubes. These images together show that the surface of the control group TNTs has a uniform structure and composition. Figure 1 , Figure 2 , Figure 3 The effects of surface treatments of S-TNTs, H-TNTs, and R-TNTs (S / H / R-TNTs) on the surface characteristics and performance of TNTs are shown. Surface characterization by OM, SEM, RR, and EDS, combined with quantitative analysis of diameter, surface roughness (Ra), and contact angle (WCA). In OM and SEM images ( Figure 1 A, Figure 2 A, Figure 3 A) Different series (S-TNTs, H-TNTs and R-TNTs) and size parameters (50, 150, 300, 600) ( Figure 1 A, Figure 2 A, Figure 3 The sample surface of A) shows different microstructures, ranging from uniform grids to hexagonal and circular arrangements. SEM images ( Figure 1 A, Figure 2 A, Figure 3 A) Further revealing the interface between TNTs and the treated area (AHT), the surface has raised and depressed areas, in which the TNTs structure occupies the depressed part, which is a more ordered and smooth tubular structure. These observations confirm the successful preparation of the layered coating of S-TNTs, H-TNTs, and R-TNTs, which meets the design goals. The EDS spectrum shows the distribution of titanium (Ti) and oxygen (O), confirming that the sample surface is mainly composed of TNTs. Figure 1 D, Figure 2 D, Figure 3D, the surface roughness of the control group TNTs is the lowest. In contrast, the surface roughness of the TNTs samples modified by micropatterning is significantly different from that of the control group TNTs (p<0.05). As the diagonal diameter increases, the Ra values ​​of each series generally increase, but there is a certain decreasing trend at the maximum (600), suggesting that excessive micropatterning size may lead to surface smoothing. Figure 1 E, Figure 2 E, Figure 3 The E control group TNTs showed the smallest contact angle, which was significantly different from all S-TNTs, H-TNTs and R-TNTs (S / H / R-TNTs) samples (p<0.05), which may be due to the increase in surface roughness, which improves the hydrophobicity.

[0063] Example 2 Stability Test

[0064] 1. Peel test

[0065] To evaluate the mechanical stability of the coating, a peel test was performed according to the GBT228.1-2010 metal material tensile test standard. A universal testing machine (Instron, USA, model 3369) was used to apply a standard tape at a speed of 1 mm / min to apply tension. After the test, all coatings showed signs of impaired integrity. The morphology of the peeled portion was examined by OM, SEM, and RR.

[0066] In clinical applications, cracking and delamination of TNTs coatings due to mechanical stress and wear may trigger an immune inflammatory response in the host, ultimately leading to implant failure. Therefore, the mechanical stability of the coating is particularly important for implants with complex shapes. Conventional single-layer “smooth” coatings do not provide sufficient wear and crack resistance to withstand chewing pressure. Therefore, layered coating technology has been proposed to meet these performance requirements. This section focuses on the stability of TNTs and modified coatings of S-TNTs, H-TNTs, and R-TNTs (S / H / R-TNTs), especially their adhesion strength and wear resistance.

[0067] like Figure 4 As shown in B1, this experiment evaluated the bonding strength between different coatings and titanium substrates by sticking tape on TNTs and S-TNTs, H-TNTs and R-TNTs (S / H / R-TNTs) samples and then peeling off the tape to perform a pull-off adhesion test, using the maximum tensile force required for coating delamination as the evaluation standard. OM, SEM, RR analysis test results ( Figure 4B2), OM, RR show the peeling area, and the clear area boundary indicates the degree of adhesion failure, which is important for evaluating the surface adhesion performance of TNTs under mechanical stress. SEM shows the structure of peeled TNTs. These observations together indicate that the peeling process effectively characterizes the adhesion quality of TNTs.

[0068] According to the results in the figure, the peeling tests of S-TNTs, H-TNTs and R-TNTs under different treatment conditions show that the surface pattern has a significant effect on the peeling force ( Figure 5 A. Figure 6 A and Figure 7 A). The morphology of the S-TNTs, H-TNTs and R-TNTs peeling regions of each group of samples under different treatment conditions is shown by OM, SEM and RR. OM shows that the micro-hexagonal pattern group has the most abundant residual structure. The SEM image shows that in the micro-hexagonal pattern group, the number of remaining TNTs structures is the largest, and the delamination area shows a regular and neat honeycomb nanopore structure. Figure 5 B, Figure 6 B, Figure 7 The graph in Part B shows the force-displacement curves of different samples during the peeling process. The peeling forces of different groups of samples in the mechanical test are different, reflecting the difference in adhesion performance of different surface structures. As the pattern size and structure change, the peeling force also changes. Figure 5 C, Figure 6 C, Figure 7 C compared the maximum peel force (FM) of each group of samples, and the control group TNTs coating had the lowest delamination force. In contrast, the delamination force required for all modified S-TNTs, H-TNTs, and R-TNTs coatings increased, and their anti-delamination performance was statistically significantly different from that of the control group TNTs (p<0.05), thereby enhancing the overall anti-delamination performance of the coating. These results show that specific pattern design can enhance the surface adhesion performance of TNTs, and the optimized surface structure has potential in improving material adhesion. The possible reason is that the layered structure delays the displacement movement more effectively due to the increase in the number of interfaces and the shortening of the period, thereby effectively hindering the propagation of cracks. The critical load and shear force required for coating delamination increase, thereby improving the adhesion strength of the layered coating.

[0069] 2. Friction and wear behavior

[0070] In this experiment, the wear resistance of the coating was evaluated by friction and wear testing. When the implant is embedded in the bone tissue and begins to bear chewing pressure, micro-motion may occur at the interface due to the difference in elastic modulus between the implant and the bone tissue, which will cause wear of the implant surface coating and affect bone integration. This study conducted wear tests in three different microenvironments (dry environment, Hanks balanced salt solution simulated body fluid environment, artificial saliva simulated oral environment) to deeply explore the stability of TNTs and modified S-TNTs, H-TNTs and R-TNTs (S / H / R-TNTs) coatings.

[0071] Figure 4 C1 shows a schematic diagram of a friction and wear test using a grinding ball to apply friction to samples containing TNTs and S-TNTs, H-TNTs, and R-TNTs (S / H / R-TNTs). Figure 4 C2 shows the surface morphology of the control group TNTs after wear under three different environmental conditions. A typical pear-shaped wear mark is formed on the surface of the sample. Under dry conditions, the wear mark is obvious and there are a lot of black wear debris on the edge; under lubricated conditions (Hanks and AS simulate normal physiological environment), the wear mark is reduced and the edge is relatively complete; in AS solution, the wear mark is the smallest and the edge is the smoothest.

[0072] Figure 8 A, Fig. 9 A, Fig.10 Figure A shows the friction and wear surface morphologies of S-TNTs, H-TNTs and R-TNTs (S / H / R-TNTs) with different surface structures in dry, HBSS and AS environments. The morphologies are similar to those of the control group, but the wear scar width is reduced and the wear mark edge is intact. Figure 8 B, Fig. 9 B, Fig.10 B and Figure 8 C, Fig. 9 C, Fig.10 C shows the wear width and average friction coefficient of different structures under different environments. The analysis results show that no matter what the environment, the friction coefficient curve, average value and wear scar width (indicating the amount of wear) show that the friction coefficient and wear scar width of the control group TNTs are the largest. Compared with the control group TNTs, all modified S-TNTs, H-TNTs and R-TNTs (S / H / R-TNTs) coatings showed significant statistical differences in friction and wear resistance (p<0.05), showing lower friction coefficients and narrower wear scars, thereby enhancing the overall performance of the coating.

[0073] The improved convex-concave structure of S-TNTs, H-TNTs and R-TNTs (S / H / R-TNTs) effectively reduces the ball-disk contact area, helps to relieve stress concentration in the contact area, reduces the overall stress in the contact area, reduces surface wear, and improves friction performance. It may also be because the wear mainly includes adhesive wear and three-body wear, in which the proportion of three-body wear is directly related to the amount of wear. On the surface of the smooth TNTs sample, the wear debris accumulates as a third body during the friction process, resulting in three-body wear under cyclic rolling, aggravating the surface wear, forming deeper pear-shaped wear marks and generating a large amount of debris. Compared with the "flat" and "smooth" TNTs samples, the S / H / R-TNTs samples with improved convex-concave structures reduce three-body wear and reduce the surface friction coefficient by effectively capturing the wear debris in the grooves. The accumulation of surface debris is effectively reduced, thereby reducing the occurrence of surface three-body wear and reducing the width of the wear mark.

[0074] The results of the average friction coefficient also show that different surface structures S-TNTs, H-TNTs and R-TNTs (S / H / R-TNTs) exhibit better wear resistance and lower friction coefficient in a lubricated environment (Hanks and AS, simulating a normal physiological environment). Under liquid lubrication conditions, the modified S / H / R-TNTs not only capture wear debris, but also store lubricants, effectively reducing three-body wear and adhesive wear. This not only forms a lower and more stable friction coefficient, but also reduces the amount of wear, achieves continuous lubrication and enhances wear resistance.

[0075] Example 3 In vitro osteogenesis test

[0076] In the in vitro osteogenesis test, mouse preosteoblast cell line MC3T3-E1 (ATCC, China) was used. Cells were cultured in α-MEM medium (Gibco, USA), which contained 10% fetal bovine serum (FBS, Gibco, USA) and 1% penicillin / streptomycin (PS, Gibco, USA). The culture conditions were maintained at 37°C, in a humidified environment of 5% CO2. Cells were passaged when they reached 80-90% confluence. Before starting any in vitro experiments, all samples were sterilized by immersion in 75% ethanol solution for 30 minutes and then air dried.

[0077] Cell morphology, early adhesion and viability assays

[0078] Cell morphology was observed using an inverted fluorescence microscope (IFM, OLYMPUS IX71, Japan). MC3T3-E1 cells were plated at 8×10 3The cells were cultured in 24-well plates at a density of 10 cells / mL for 3 days. Subsequently, the samples were washed and fixed in 4% paraformaldehyde, and the cells were labeled with fluorescein isothiocyanate (FITC)-phalloidin and 4′,6-diamidino-2-phenylindole (DAPI) for morphological observation.

[0079] To evaluate cell adhesion, fluorescent staining was performed. MC3T3-E1 cells were plated at 2 × 10 4 cells / mL in a 24-well plate. After 3 h of incubation on the samples, the cells were washed, fixed, and stained with DAPI to visualize the cell nuclei. Observation was performed by IFM and further analysis was performed using Image J software. The viability of MC3T3-E1 cells on each sample was assessed by MTT assay. Cells were plated at 2 × 10 4 After culturing in 24-well plates for 4 and 7 days, the samples were rinsed with PBS. Subsequently, 300 μL of incomplete culture medium and 30 μL of MTT solution were added to each well and incubated at 37°C for 4 hours. Then 1 mL of DMSO was added to dissolve the formazan crystals. The optical density of the solution was measured at a wavelength of 490 nm using a microplate reader (Bio-Rad 680, USA).

[0080] To investigate the effect of coatings on osteoblast biocompatibility, MC3T3-E1 cells were co-cultured on TNTs and S-TNTs, H-TNTs and R-TNTs (S / H / R-TNTs) coatings, respectively. Cell biological functions were evaluated by 3h adhesion staining and analysis, 3-day morphology staining, 4-day and 7-day MTT assay, ALP assay, and 14-day mineralization staining and assay.

[0081] according to Figure 4 D. Fig.11 A, Fig.12 A, Fig.13 A, Results, TNTs and S-TNTs, H-TNTs and R-TNTs (S / H / R-TNTs). The images of each group show the cell growth at different time points (3 hours, 3 days and 14 days). The cell morphology is also affected by the Micro-Pattern, and the distribution of MC3T3-E1 cells is consistent with the Micro-Pattern. Because according to the contact guidance theory, when cells grow on nanometer to micrometer scale patterns, they will adjust their growth direction and grow along the pattern direction.

[0082] The results of adhesion, MTT and ALP quantitative analysis at 4 and 7 days showed that ( Fig.11 BF, Fig.12 BF, Fig.13 BF, Figure 4D) S-TNTs, H-TNTs, and R-TNTs (S / H / R-TNTs) coatings maintained at least comparable adhesion, activity, and ALP expression levels to those of control TNTs. Mineralization staining and quantitative analysis at 14 days showed that compared with control TNTs, the 300 μm S / H / R-TNTs group ( Fig.11 G, Fig.12 G, Fig.13 G, Figure 4 D) and compared with the control group TNTs, there was a statistically significant difference (P < 0.05), which means a higher calcium content and a more effective osteogenic effect.

[0083] This experiment also analyzed the biological properties between each group and pure titanium, TNTs, and S / H / R-TNTs. The results showed that there were significant statistical differences between each group and the pure titanium group, and all of them could improve the biological properties of Ti.

[0084] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A titanium-based dental implant, the surface of which is modified with a mechanically stable TNTs film by photolithographic micropatterning.

2. A method for preparing a mechanically stable TNTs film by photolithographic micropatterning, comprising the following steps: (1) performing alkali heat treatment on the surface of the titanium-based material; (2) spin coating a photoresist on the surface of the titanium-based material subjected to alkali heat treatment; (3) Use a mask to cover the photoresist and expose it with ultraviolet light; (4) soaking the exposed titanium-based material in a developer; (5) soaking the titanium-based material obtained in step (4) in an etching solution, and then ultrasonically cleaning and baking; (6) anodizing the etched area; (7) removing the photoresist to obtain a photolithographically micropatterned mechanically stable TNTs film; The mechanically stable TNTs film surface structure formed by photolithographic micropatterning is that TNTs are embedded in the grooves formed by etching.

3. The method for preparing a mechanically stable TNTs film according to claim 2, characterized in that: The micropattern is square, hexagonal and circular, and optionally, the diagonal diameter of the micropattern is 50-600 μm; Optionally, the depth of the stripe pattern is 10-50 μm, preferably, the depth of the stripe pattern is 20 μm.

4. The method for preparing a mechanically stable TNTs film according to claim 2, characterized in that: The ultraviolet light wavelength used for the ultraviolet light exposure is 365nm, and the exposure time is 30-120 seconds, preferably, the exposure time is 90 seconds.

5. The method for preparing a mechanically stable TNTs film according to claim 2, characterized in that: The alkaline heat treatment step in step (1) is to use 1-10 mol / L NaOH solution for treatment at 70-90° C. for 12-48 hours. Preferably, the concentration of the NaOH solution is 5 mol / L, the temperature is 80° C., and the treatment time is 24 hours.

6. The method for preparing a mechanically stable TNTs film according to claim 2, characterized in that: The etching solution comprises deionized water, nitric acid and hydrofluoric acid, and the ratio of deionized water, nitric acid and hydrofluoric acid is 1:1:9; optionally, the immersion time of the developer in the step (4) is 5-10 minutes, preferably, the immersion time of the developer is 8 minutes.

7. The method for preparing a mechanically stable TNTs film according to claim 2, characterized in that: The electrolyte used for anodization in step (6) includes deionized water, glycerol and ammonium fluoride, and the ratio of deionized water, glycerol and ammonium fluoride is 50:50:

1. Optionally, the voltage of anodization in step (6) is 10-100V, and the time is 0.5-1.5h. Preferably, the voltage of anodization is 30V, and the time is 1h.

8. The method for preparing a mechanically stable TNTs film according to claim 2, characterized in that: The step of spin coating the photoresist in step (2) is to use a spin coater to spin coat 5-15 μL of the photoresist at a speed of 2000-4000 rpm for 10-50 seconds to coat the micro-patterned TNTs sample.

9. The photolithographically micropatterned mechanically stable TNTs film obtained by the method for preparing the photolithographically micropatterned mechanically stable TNTs film according to claims 2-8.

10. Use of the photolithographically micropatterned mechanically stable TNTs film prepared by the preparation method described in claims 2-8 or the photolithographically micropatterned mechanically stable TNTs film described in claim 9 in improving the wear resistance and osteogenic differentiation ability of titanium implants.

Citation Information

Cited By

  • Preparation method of medicinal aluminum foil

    CN119925166A

  • A method for preparing medicinal aluminum foil

    CN119925166B